The Association of Valacyclovir Prophylaxis with the Suppression of Recurrent Genital Herpes: A Systematic Review - Indra Hadi Rapmartua Ompusunggu; Desty Friska Kurnia (International Medical Journal Corp. Ltd, 2025)
Introduction : Recurrent genital herpes (RGH), a chronic condition primarily caused by Herpes Simplex Virus type 2 (HSV-2), represents a significant global health concern, imposing a substantial clinical and psychosocial burden on affected individuals (Fife et al., 2007; Romanowski, Marina and Roberts, 2003). Valacyclovir, a prodrug of acyclovir with enhanced oral bioavailability, is a cornerstone of pharmacological management (Baker et al., 1999). This systematic review aims to critically evaluate and synthesize the evidence from randomized controlled trials (RCTs) regarding the efficacy and safety of valacyclovir prophylaxis for the suppression of RGH. Methods : A systematic search of PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov was conducted to identify relevant RCTs. Studies were included if they evaluated daily suppressive valacyclovir therapy against placebo, another antiviral, or a different valacyclovir dose in adults with RGH. The study selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data on study design, participant characteristics, interventions, and predefined outcomes were extracted. The methodological quality of each included study was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool (Sterne et al., 2019). Results : Seventeen RCTs met the inclusion criteria. The evidence consistently demonstrates the superiority of valacyclovir over placebo in suppressing RGH. A network meta-analysis showed a significantly lower risk of having at least one clinical recurrence with valacyclovir versus placebo (Le Cleach et al., 2014). Suppressive therapy reduces the frequency of genital herpes recurrences by 70%-80% (Centers for Disease Control and Prevention, 2021). It also potently reduces total genital HSV shedding by up to 78% (Martens et al., 2009) and decreases the risk of HSV-2 transmission to susceptible heterosexual partners by approximately 48% (Corey et al., 2004). Compared to acyclovir, valacyclovir offered comparable clinical efficacy with the convenience of less frequent dosing (Reitano et al., 1998; Public Health Agency of Canada, 2024). In specific populations, valacyclovir prophylaxis initiated at 36 weeks of gestation significantly reduced recurrences at delivery (Hollier and Wendel, 2008), and a twice-daily regimen was found to be most effective for HIV-coinfected individuals (DeJesus et al., 2003; Warren, Harris and Brennan, 2004). Patient-reported outcomes strongly favored suppressive therapy over episodic treatment, with significant improvements in quality of life and treatment satisfaction (Romanowski, Marina and Roberts, 2003). The long-term safety profile of valacyclovir was favorable and comparable to placebo (Brown et al., 2005; Reitano et al., 1998). Discussion : The synthesized evidence confirms the high efficacy of valacyclovir prophylaxis, which stems from its advantageous pharmacokinetic profile (Baker et al., 1999). The enhanced bioavailability of valacyclovir allows for a simplified once-daily dosing regimen, which improves patient adherence and overall quality of life (Romanowski, Marina and Roberts, 2003). The potent suppression of virologic shedding is the key mechanism underlying both the reduction in clinical recurrences for the individual and the significant public health benefit of reduced sexual transmission (Corey et al., 2004; Martens et al., 2009). The evidence supports an individualized dosing strategy based on recurrence frequency and host immune status (Reitano et al., 1998; Warren, Harris and Brennan, 2004). Conclusion : Valacyclovir prophylaxis is a highly effective, safe, and well-tolerated first-line intervention for the management of recurrent genital herpes. It significantly reduces clinical and virologic manifestations of the disease, improves patient quality of life, and serves as a critical tool for reducing sexual transmission.